52nd AIAA/SAE/ASEE Joint Propulsion Conference 2016
DOI: 10.2514/6.2016-4537
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Applied-Field Component of the Thrust of a Lithium Lorentz Force Accelerator

Abstract: The operation of an inverted-pendulum thrust stand designed to directly measure the applied-field thrust component of a steady-state applied-field magnetoplasmadynamic thruster is presented. This measurement, which is necessary for improving and validating thrust models, is achieved by mechanically isolating the solenoid from the thruster so that the solenoid can move independently. The deflection of the solenoid is compared to deflection by known forces to determine the applied-field thrust component. The thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…There is a power regime for each component when that component MPDTs, and it is caused by the current's interaction with its own self-induced magnetic field. In AF-MPDTs, the SF thrust component is often dominating at high power [12]. Brittany Lee Ilardi in their report found that current runs radially from the anode toward the cathode in a classic self-field MPDT, then axially down the cathode.…”
Section: Detailed Study Of Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a power regime for each component when that component MPDTs, and it is caused by the current's interaction with its own self-induced magnetic field. In AF-MPDTs, the SF thrust component is often dominating at high power [12]. Brittany Lee Ilardi in their report found that current runs radially from the anode toward the cathode in a classic self-field MPDT, then axially down the cathode.…”
Section: Detailed Study Of Limitationsmentioning
confidence: 99%
“…Self-Field MPD (William J. Coogan et al, 2016) studied that in an MPDT, there are three thrust generating mechanisms: Self-field (SF), Gas dynamic (GD), Applied-field (AF). There is a power regime for each component when that component MPDTs, and it is caused by the current's interaction with its own self-induced magnetic field.…”
Section: Detailed Study Of Limitationsmentioning
confidence: 99%
See 1 more Smart Citation